EDUCATION SANDBOX POLICY MANAGEMENT STRATEGY FOR DEVELOPING THE QUALITY OF EDUCATION SUSTAINABLY - Palachai, Sompong; Vehachart, Rungchatchadaporn (Journal of MCU Nakhondhat, 2026)
This research aims to examine the education sandbox policy management strategy for sustainably improving the quality of education. This research employed a qualitative approach, using a document analysis form developed from a conceptual framework for the education sandbox policy management. The form underwent content validity testing by three experts. Data collection and analysis involved examining 20 strategic plans for the education sandbox across 20 pilot provinces from 2019 to 2025. The selected documents were chosen explicitly for their relevance, reliability, and timeliness. Qualitative data analysis techniques were employed. The research findings revealed that the policy management strategies for the education sandbox to develop sustainable educational quality comprise nine strategic issues: educational innovation development, reducing inequality and creating educational opportunities, spatial management, student quality development, collaboration and network building, educational decentralization, school curriculum development, teacher and educational personnel capacity building, and promoting and supporting educational quality assurance systems. The findings indicate that the policy strategies for the education sandbox align with spatial educational management and Sustainable Development Goal 4 (SDG4) to improve educational quality, create opportunities, and reduce educational inequality, ensuring inclusiveness, equity, and lifelong learning. Furthermore, the developed document synthesis model. The synthesized results can serve as a framework for formulating policy proposals and strategic/action plans for agencies and educational institutions in the area, aligned with the education sandbox and sustainable development.